ENT600: ILUCA / Afifah Abdul Razak … [et al.] - Abdul Razak, Afifah; Mohd Shafie, Khalid; Abdul Rahman, Abdul Azim; Abdul Malik, Abdul Azim; Nik Mohd Rosli, Nik Ahmad Usamah (2014)
Iluca is an action camera that combines the function of a camera and a projector in one product. It is practical for travellers, extreme sports enthusiasts, designers, educators and students for indoor and outdoor activities as this product offers the solution of disability to present on-the-go and the function of projecting VR videos and images. Nowadays,.a more portable, compact, and multifunction device are in demand. Activities that enable users to simplify the capturing, editing and presenting photos, videos and virtual reality (VR) materials, all in one would be an interesting project and soon a reliable gadget. The team has come out with a product that is believed to be able to contribute to those demands that is Iluca. The existing of compact action cameras in the market nowadays simplifies the capturing of moments, but lacking in the function to properly present to the audience while on-the-go may disrupt those priceless moments.